Research structure of abstracts on women’s health presented in a brazilian nursing congress - Andrea Gomes Linard; Dafne Paiva Rodrigues; Maria Albertina Rocha Diógenes; Maria de Nazaré de Oliveira Fraga; Marta Maria Coelho Damasceno (Rev Rene)
Descriptive and documental study that analyzes the research abstracts about women’s health concerning the structure of its composition. It was used as source material 159 research abstracts on the subject matter referred to, published in CD ROM and in Book-summary of a Brazilian Nursing Congress. For data collection, it was used a form that refers to the composition structure rising, being taken into account the complete, partial presence or even absence of the essential elements extolled by the Norms of ABNT – NBR 6028/90. The results revealed that among the summaries 62.3% were complete, 29.5% were incomplete type I and 8.2% were incomplete type II. The conclusion is that the research summaries presented error flaws in its elaboration, repeating the presence of summaries badly elaborated already verified in other recent studies.